2018
DOI: 10.1177/0040517518798646
|View full text |Cite
|
Sign up to set email alerts
|

Bi-stretch auxetic woven fabrics based on foldable geometry

Abstract: The fabrication of auxetic fabrics by using conventional yarns and machinery has gained extraordinary interest from researchers in recent years. However, to date this approach has only been adopted to fabricate auxetic knitted fabrics and uni-stretch auxetic woven fabrics. This paper reports a study that aimed to develop a new class of bi-stretch woven fabrics with auxetic behavior using conventional elastic and non-elastic yarns, and available weaving machinery. Bi-stretch auxetic woven fabrics were firstly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 28 publications
0
69
0
Order By: Relevance
“…By parameterizing the folded fabric previously investigated by Cao et al and Zulifqar et al, a folded model was built, as shown in Figure . The folded structure can be considered as a thin‐walled structure without any voids.…”
Section: Model and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By parameterizing the folded fabric previously investigated by Cao et al and Zulifqar et al, a folded model was built, as shown in Figure . The folded structure can be considered as a thin‐walled structure without any voids.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Grima et al demonstrated that the graphene could be made to mimic the behavior of the wrinkled paper model to exhibit auxetic properties. In particular, the folded geometry, as shown in Figure a, has been successfully transformed to NPR fabrics (Figure b) by Cao et al and Zulifqar et al This kind of fabrics could also be considered as a nonporous sheet or membrane and they were realized by creating the phenomenon of differential shrinkage into a fabric structure to enable different sections of a fabric unit cell to endure different levels of shrinkage upon relaxation. The relaxed fabric in Figure b can be divided into two sections: the loose weave zigzag area and the tight weave zigzag area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cao et al 12 reported that the optimization of spinning parameters could influence the hairiness properties of polyester cotton vortex yarn.…”
Section: Introductionmentioning
confidence: 99%
“…17 Researcher also reported that manmade fibers are made up of different polymer ingredients and these ingredients are made up of long chain polymer. 18…”
Section: Introductionmentioning
confidence: 99%